Hi! I’ve been trying to solve this. The answer is C, but I thought the roots have to be a pair and then add up to b (in this case, k). So, that would need to be -2, given that the problem gives you the information that one of the roots is 3.

What does K being a constant mean in this context?

Thank you so much!!

If roots are given then the easiest way is to plug and solve it:

x^2+kx-6=0

Plugging x=3

3^2+3k-6=0

9-6+3k=0 \text{ or }3+3k=0

3k=-3 \text{ or }\textbf{k=-1}

3+3(-1) =0

0=0

1 Like

Thank you so much!!